About exploring vago-sympathetic system - O. Llerena, Jorge (1925)
Medical science, in its quest for renewal and unceasing progress holds for us, day after day, amazing news. What until yesterday we had really built as a scientific medical heritage, collapses today impulse lush detached inductions increasingly conditional experiments precisely that on the ruins of the defunct raise new buildings, sometimes ephemeral duration, and others, as solid moles, which challenge the times. But precisely in this mutation, this evolution is the secret of scientific progress, and must be respected.